Field Survey and Geological Effects of the 15 November 2006 Kuril Tsunami in the Middle Kuril Islands - MacInnes, B. T.; Pinegina, T. K.; Bourgeois, J.; Razhigaeva, N. G.; Kaistrenko, V. M.; Kravchunovskaya, E. A. (Pure and Applied Geophysics, 2009)
The near-field expression of the tsunami produced by the 15 November 2006 Kuril earthquake (M-w 8.1-8.4) in the middle Kuril Islands, Russia, including runup of up to 20 m, remained unknown until we conducted a post-tsunami survey in the summer of 2007. Because the earthquake occurred between summer field expeditions in 2006 and 2007, we have observations, topographic profiles, and photographs from three months before and nine months after the tsunami. We thoroughly surveyed portions of the islands of Simushir and Matua, and also did surveys on parts of Ketoi, Yankicha, Ryponkicha, and Rasshua. Tsunami runup in the near-field of the middle Kuril Islands, over a distance of about 200 km, averaged 10 m over 130 locations surveyed and was typically between 5 and 15 m. Local topography strongly affected inundation and somewhat affected runup. Higher runup generally occurred along steep, protruding headlands, whereas longer inundation distances occurred on lower, flatter coastal plains. Sediment transport was ubiquitous where sediment was available-deposit grain size was typically sand, but ranged from mud to large boulders. Wherever there were sandy beaches, a more or less continuous sand sheet was present on the coastal plain. Erosion was extensive, often more extensive than deposition in both space and volume, especially in areas with runup of more than 10 m. The tsunami eroded the beach landward, stripped vegetation, created scours and trim lines, cut through ridges, and plucked rocks out of the coastal plain.
id: 831; 418XP Times Cited:2 Cited References Count:46Y